8-Phenyl-10-oxa-8-azatricyclo[4.3.0.1(2,5)]decane-7,9-dione - Zhu, Wen-Zhong (International Union of Crystallography, 2009)
The reaction of aniline with norcantharidin produced the imide title compound, C(14)H(13)NO(3), which shows no significant hydrogen bonds in the crystal structure. The dihedral angle between the phenyl and pyrrolidine rings is 48.48 (6)°.